KEJAHATAN AKUNTANSI DALAM KAITANNYA DENGAN UNDANG-UNDANG NOMOR 5 TAHUN 2011 TENTANG AKUNTAN PUBLIK - Herman Fikri (Jurnal Hukum Mimbar Justitia, 2016)
A Certified Public Accountant has an important role in improving the quality and credibility of financial information or financial report of an entity. A public accountant has task in carrying out public confidence to provide an opinion on the financial statements of an entity. Thus, the responsibility of A Public Accountant lies on their opinion or statement on financial information of an entity, while the presentment of report or financial information is the managerial responsibility.Frequently, the accounting scandals are influence by politics and business, which appeared by the disclosure of misdeeds executives of public companies. This crime typically involve complex methods for misusing funds or misleading, exaggerating revenue, reducing cost, overstating the value of corporate assets or reducing the amount of obligations, sometimes they are working with the officials in other companies or affiliates. By referring the meaning of accounting scandals above, accounting crimes tend to be fraudulent statement (fraud whose regarding to the presentation of financial statements).Keywords: Accounting Scandals, Crimes, Companies, Politics, and Public.